Black Holes - Dotti, Gustavo (Cadernos de Astronomia, 2023)
An elementary introduction to General Relativity and the concept of Black Holes is given assuming a basic knowledge of Physics, and leaving as footnotes any advanced technical comment. A brief historical introduction of the black hole concept is given, and the notable recent experimental advances are commented: the detection of gravitational waves by LIGO in 2015 and the recently disclosed Event Horizon Telescope images.